SANKSI PELAKU NUSYUZ (Studi Pandangan Mazhab Syafi'i & Amina Wadud) - T.Dahlan Purna Yudha (State of Islamic Institute Langsa, 2017)
Nusyuz etymolically means opposition, hate, while according to the term nusyuz is the conduct of wife who opposes her husband to not carry out his orders, turn away from her husband and make the husband angry. Nusyuz according to the School of Shafi'i is the release of wife’s obedience to her husband. Either disobedience which is indicated by words or through behavior (deeds) or both (words and deeds) at once. According to Imam al-Shafi'i and some jurists from the Shafi'i School, the sanctions imposed for the perpetrators of the Nusyuz, as legitimized in QS al-Nisa: 34, were taken through three levels of advising, separating the bed, striking. Amina wadud interpret nusyuz as a disturbance of household harmony. Amina Wadud does not agree if nusyuz is meant by disobedience to the husband. Amina Wadud argues that nusyuz is more accurately interpreted as an unharmonious situation between married couples. Between the sect of Shāfi'ī and Amina Wadud have similarities and differences regarding the problem of sanctions that should be given to the perpetrators of nusyuz. The second equation is that they agree to the imposition of sanctions, but on the third sanction of beating this opinion is only approved by the Shafi'i school alone (though beating must be under certain conditions), whereas Amina Wadud prefers more exreme solution, that is divorce.